If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + -7x = -3 Solving -14 + -7x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -7x = -3 + 14 Combine like terms: -14 + 14 = 0 0 + -7x = -3 + 14 -7x = -3 + 14 Combine like terms: -3 + 14 = 11 -7x = 11 Divide each side by '-7'. x = -1.571428571 Simplifying x = -1.571428571
| -5.5=-0.02x^2+x+0.5 | | -5.5=-0.02x+x+0.5 | | 5(n+7)=-44+2(n+6) | | y=-0.02x^2+x+0.5 | | 2x+7-3x=1 | | y=-0.02x+x+0.5 | | 3x+27=10x-33 | | -40=33x+15 | | 3=-x+1 | | 6(2x+1)-3(5x+2)=0 | | 8=8n-22-7n | | -x+3= | | y=-0.02x+x+6 | | 7=3(x-7)+10 | | 8x=16(x-36) | | x=-5+4 | | 3x+15=6x+7 | | 3(2-a)=8-a | | 3x-8=5(2x-3) | | 147-4x=23x+21 | | 5x=(6x-3) | | 5(2x-3)+6=43-3x | | 8+12x=15x-19 | | 2c+5=3c+7 | | 67-5x=9x+7 | | 3a-11=4 | | 60-x=2(x-36) | | 2x+6=-3 | | 104-x=2(x-29) | | 20x-9x-20=0 | | 3x+139=12x-14 | | x-9x-20=0 |